Lagrangian approach in spin-oscillations problem - Pyshkin, P.V.; Kopeliovich, A.I.; Yanovsky, A.V. (Condensed Matter Physics, 2014)
Lagrangian of electronic liquid in magneto-inhomogeneous micro-conductor has been constructed. A corresponding Euler-Lagrange equation has been solved. It was shown that the described system has eigenmodes of spin polarization and total electric current oscillations. The suggested approach permits to study the spin dynamics in an open-circuit which contains capacitance and/or inductivity.